Comparative Justice Accountability of Samen Leven Actors in Indonesia and Malaysia - Saputri, Atha Difa; Julianto, Ricky (Faculty of Law, Universitas Negeri Semarang, 2023)
The phenomenon of samen leven, or cohabitation, challenges traditional religious and cultural norms in Indonesian society, yet it has become increasingly prevalent in contemporary times, particularly in Indonesia and Malaysia. This trend suggests a shifting landscape where moral and religious values are undergoing transformation. This article delves into the regulatory frameworks surrounding cohabitation, examining provisions within both current and proposed Criminal Codes, and explores the ensuing debates and controversies. Additionally, it scrutinizes the legal, religious, and social perspectives on cohabitation, along with the associated sanctions. The primary objective of this paper is to comprehensively understand the legal stance on cohabitation and explore measures to address the issue of samen leven in Indonesia, achieved through a comparative analysis of legal systems between Malaysia and Indonesia. The research employs a combination of literature review and normative juridical methods, relying on primary sources such as the Criminal Code, Marriage Law No. 1 of 1974, and Malaysia's 1984 Islamic Family Law pertaining to marriage and divorce. Secondary sources encompass a wide array of legal publications, including textbooks, legal dictionaries, journals, articles, and case commentaries. By critically examining the legal frameworks and social contexts surrounding cohabitation, this study aims to provide insights into the divergent approaches adopted by Malaysia and Indonesia. Such insights are pivotal for developing effective strategies and policies to address the challenges posed by cohabitation while navigating the complexities of religious, cultural, and legal landscapes in both countries.